Extraction of Sulfur Compounds from Model Petroleum Products using Fe3 O4 Nanoparticles and Acetic Acid-1-Butyl-3-Methylimidazolium Chloride based on Deep Eutectic Solvents - Maaroof, Yousif T.; Qader, Idrees B.; Ismail, Hani K.; Hamad, Hardi Q.; Taher, Sardasht R. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
This research demonstrates that deep eutectic solvents (DESs) can eliminate sulfur compounds, which are corrosive and carcinogenic species, from model petroleum products through liquid-liquid extraction. Several monoprotic acids, including formic acid and acetic acid, are used to make DESs, along with 1-butyl-3-methylimidazolium chloride (BmimCl) as a hydrogen bond acceptor. These DESs are used for the first time to remove sulfur compounds (thiophene and dibenzothiophene) from an alkane as a model hydrocarbon (n-octane), which is used instead of crude oil as the latter contains a variety of species, including nitrogen compounds, hydrocarbons, and oxygen. The optimal parameters for the removal of sulfur are discussed, including the extraction temperature, reaction time, and mass ratio of DES to the model hydrocarbon, whilst the regeneration of DESs is also considered. H2O2 and iron oxide (Fe3O4) are also used as nanoparticle (NP) catalysts to enhance the sulfur removal process. Several characterization methods, including scanning electron microscopy, Fourier transform infrared, energy dispersive X-ray, and transmission electron microscopy, are used to determine the structural characteristics of the Fe3O4 NPs. The results show that acetic acid, as a monoprotic acid-based DES, is able to remove more than 86% of the sulfur molecules from model petroleum products when the mass ratio of DES to model petroleum products is 2:1, at 30°C and within 60 min. This research provides an important opportunity to advance our understanding of the role of DESs in removing carcinogenic and corrosive particles in industrial processes.